Metabolic cooperation between cancer and non-cancerous stromal cells is pivotal in cancer progression - Lopes-Coelho, Filipa (2022)
The way cancer cells adapt to microenvironment is crucial for the success of carcinogenesis, and metabolic fitness is essential for a cancer cell to survive and proliferate in a certain organ/tissue. The metabolic remodeling in a tumor niche is endured not only by cancer cells but also by non-cancerous cells that share the same microenvironment. For this reason, tumor cells and stromal cells constitute a complex network of signal and organic compound transfer that supports cellular viability and proliferation. The intensive dual-address cooperation of all components of a tumor sustains disease progression and metastasis. Herein, we will detail the role of cancer-associated fibroblasts, cancer-associated adipocytes, and inflammatory cells, mainly monocytes/macrophages (tumor-associated macrophages), in the remodeling and metabolic adaptation of tumors.